Cardiometabolic risk factors in adults with normal weight obesity: A systematic review and meta‐analysis. Issue 4 (12th April 2022) - Rakhmat, Iis Inayati; Putra, Iwan Cahyo Santosa; Wibowo, Arief; Henrina, Joshua; Nugraha, Gaga Irawan; Ghozali, Mohammad; Syamsunarno, Mas Rizky A. A.; Pranata, Raymond; Akbar, Mohammad Rizki; Achmad, Tri Hanggono
Summary: Normal weight obesity (NWO) is a new emerging phenotype of obesity, defined as a normal body mass index with a high body fat percentage. While several studies have described the impact of NWO on cardiometabolic risk factors, the association between them remains uncertain. This meta‐analysis systematically evaluated cardiometabolic risk factors in adults with NWO compared to adults with normal weight lean (NWL). A systematic literature search was performed from the inception until September 21, 2021 in order to comprehensively search for all observational studies that had three important variables, including adults (age ≥18 years old), NWO and cardiometabolic risk factors including metabolic syndrome, hypertension, diabetes mellitus, dyslipidaemia or all laboratory findings related to cardiometabolic risk factors. Twenty‐four cross‐sectional studies with a total of 75 201 subjects are included in the qualitative and quantitative analysis. Overall, older age and female sex are more likely in NWO population. Compared to NWL, NWO is significantly associated with cardiometabolic risk factors, including metabolic syndrome (OR = 2.24 [1.74, 2.89]; p  < .001; I 2  = 76%, P heterogeneity  < 0.001), hypertension (OR = 1.60[1.36, 1.89]; p  < .001; I 2  = 76%, P heterogeneity  < 0.001), diabetes mellitus (OR = 1.72[1.54, 1.92]; p  < .001; I 2  = 47%, P heterogeneity  < 0.001), dyslipidaemia (OR = 1.50 [1.03, 2.18]; p =  .03; I 2  = 94%, P heterogeneity  < 0.001) and other laboratory findings, except for C‐reactive protein in both sexes group; and adiponectin levels in female group. Our meta‐analysis showed that NWO was associated with cardiometabolic risk factors. Thus, the traditional definition of obesity using the BMI criteria should be challenged, as those with NWO might still be exposed to a heightened risk of cardiometabolic disorders. Nonetheless, further prospective cohort studies are needed better to understand this syndrome.